Parallel Algorithms for Optimal Control of Large Scale Linear Systems - Gajić, Zoran; Shen, Xuemin (Springer London, 1993)
Parallel Algorithms for Optimal Control of Large Scale Linear Systems is a comprehensive presentation for both linear and bilinear systems. The parallel algorithms presented in this book are applicable to a wider class of practical systems than those served by traditional methods for large scale singularly perturbed and weakly coupled systems based on the power-series expansion methods. It is intended for scientists and advance graduate students in electrical engineering and computer science who deal with parallel algorithms and control systems, especially large scale systems. The material presented is both comprehensive and unique
Keywords: Engineering; Control, Robotics, Mechatronics; Appl.Mathematics/Computational Methods of Engineering; Software Engineering/Programming and Operating Systems; Communications Engineering, Networks; Software engineering; Applied mathematics; Engineering mathematics; Control engineering; Robotics; Mechatronics; Electrical engineering; Lineares System; Großes System; Regelungstheorie; Optimale Kontrolle; Schwach gekoppeltes System; Bilineares System; Paralleler Algorithmus; Optimalwertregelung; Singuläre Störung